Private sector stakeholders workshop on reviewing the draft: Nigeria agricultural strategy - Olaniyan, Babatunde (International Food Policy Research Institute, 2009)
The International Food Policy Research Institute (IFPRI) is assisting the Federal Ministry of Agriculture and Water Resources (FMAWR) in facilitating the process of updating Nigeria’s agricultural strategy with inputs from academia, the private sector, and other stakeholders. Given the invaluable role that the private sector plays in complementing the efforts of the Federal Government in promoting the growth of the economy, IFPRI in collaboration with the FMAWR with financial support from the United States Agency for International Development (USAID)/USAID MARKETS Program organized a private sector stakeholders’ workshop to review the draft agricultural strategy. The meeting was held at the Gracious Hotel in Abuja, Nigeria on April 15, 2010. The objective of the workshop was to solicit important feedback from the private sector on the draft agricultural strategy document. The workshop attracted key private and public sectors players in the agriculture industry, including the Director of the Department of Planning, Policy Analysis and Statistics (PPAS), FMAWR represented by Dr. Sunday Uhiene, former Minister of Commerce and Industry, and other key private sector players in the agriculture industry. This report summarizes the presentations, comments, main conclusions of the small group discussions, and recommendations and suggestions for moving the sector forward.